Efficient Transient Expression of Plasmid DNA Using Poly (2-(N,N-Dimethylamino) Ethyl Methacrylate) in Plant Cells - An, Zishuai; Cao, Bing; Zhang, Junzhe; Zhang, Baihong; Zhou, Chengqian; Hu, Xianglong; Chen, Wenli (Frontiers in Bioengineering and Biotechnology, 2022)
Nanomaterials have been widely studied for their potential to become the new generation of nanocarriers in gene transfection, yet it remains still difficult to apply them efficiently and succinctly to plant cells. Poly (2‑(N,N‑dimethylamino) ethyl methacrylate) (PDMAEMA), which possesses temperature and pH dual sensitivity, has largely been applied in animal cells, but it is rarely involved in plant cells. Herein, as a proof-of-concept, PDMAEMA as a gene carrier is incubated with plasmid GFP (pGFP) to explore its transfection ability in plants, and cationic polymer polyethylenimine (PEI) is used as a control. pGFP were efficiently condensed into nanostructure by electrostatic interactions at N/P (amino group from cationic polymers / phosphate group from plasmid DNA (pDNA)) ratio of 15, after complexation into nanocarriers, pGFP were protected from endonuclease degradation according to the DNase I digestion assay. After incubation with protoplasts and leaves, GFP were observed with confocal microscopy in plant cells. Western blot experiments confirmed GFP expression at the protein level. Toxicity assay showed PDMAEMA had a lower toxicity than PEI. These results showed that transient expression of pGFP was readily achieved in Arabidopsis thaliana and Nicotiana benthamiana. Notably, PDMAEMA showed lower cytotoxicity than PEI upon incubation with Nicotiana benthamiana leaves. PDMAEMA exhibited great potency for DNA delivery in plant cells. This work provides us with new ideas of more concise and more effective methods for plant transformation.